Vehicle routing problem and related algorithms for logistics distribution: a literature review and classification - Konstantakopoulos, Grigorios D.; Gayialis, Sotiris P.; Kechagias, Evripidis P. (Operational research, 2022)
The scheduling of deliveries and the routing of vehicles are of great importance for supply chain operations, as both determine to a great extent the distribution costs, as well as customer satisfaction. The fact that the distribution of goods is being affected by multiple factors, stemming from the demands of transportation companies, customers, and the external environment, has made the vehicle routing problem (VRP) among the most studied topics in operational research. These factors are transformed either to constraints or variables of the problem and finally lead to the creation of different variants of the VRP, formulated and studied by researchers. Moreover, the management of logistics and supply chain operations is being enhanced by the use of algorithms, integrated into information systems, enabling the optimization of real-life distribution cases. This paper presents a methodology for classifying the multiple VRP variants related to freight transportation, that most logistics and distribution companies face in their daily operations, as well as the algorithms solving the various problems. The application of the research methodology concluded to 334 papers, which were further sorted to 263 papers on the subject of freight transportation, aiming to identify the trends of the VRP variants and the applied algorithms, during the last decade. The correlation between the VRP variants and the applied algorithms is also identified. Finally, the paper presents the quantitative and qualitative results of the literature review and discusses the scientific publications with a significant impact on the research community.